The Effect of Applying the Uppsala Internationalisation Model in Japan: Case Study of Carrefour and Wal-Mart - Huang, Shaw-Chyi (2017)
Japan as a difficult and potential market to entry, yet some retailers still successfully survive until 2017. This dissertation will use the Uppsala Internationalisation Model to explain how retailers apply it in choosing entry modes to successfully survive in Japanese market. Besides, the types of market entry strategy might be suitable for foreign retailers to apply in Japanese retailing market will be evaluated, and the dissertation will discuss about what factors in Japan might potentially force foreign retailers to follow the Uppsala Model to gain entry to Japan as well. By means of comparing the cases of Carrefour and Wal-Mart in Japan, this dissertation verified that the Uppsala Internationalisation Model can enhance the survival possibility in Japanese market. Because the cultural differences and retail perceived knowledge between Japanese and western markets had a substantial gap, thus foreign retailers had difficulties to satisfy sophisticated Japanese consumers. Finally, the dissertation suggests that other possible choices of entry strategy, for example, International Internet Marketing (IIM) or international joint ventures might be adoptable for the failed case and other international retailers who have plans to enter Japanese market.